2007
DOI: 10.1038/sj.bjc.6603805
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma after radiotherapy: a cohort study of 332 163 Finnish cancer patients

Abstract: We evaluated the risk of angiosarcoma after radiotherapy among all patients with cancers of breast, cervix uteri, corpus uteri, lung, ovary, prostate, or rectum, and lymphoma diagnosed in Finland during 1953Finland during -2003, identified from the Finnish Cancer Registry. Only angiosarcomas of the trunk were considered, this being the target of radiotherapy for the first cancer. In the follow-up of 1.8 million person-years at risk, 19 angiosarcomas developed, all after breast and gynaecological cancer. Exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 10 publications
0
42
1
2
Order By: Relevance
“…2 Pelvic angiosarcoma is very rare; a few cases of uterine, cervical, and vaginal angiosarcoma have been reported in the literature, always in patients who underwent pelvic radiation for gynecological cancers. 11 Histologically, angiosarcoma is composed of irregular anastomosing vascular channels and exhibits an invasive growth pattern, with frequent mitotic figures, cellular pleomorphism, and areas of necrosis. Masson's tumor, instead, presents a single layer of endothelial cells without nuclear anaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…2 Pelvic angiosarcoma is very rare; a few cases of uterine, cervical, and vaginal angiosarcoma have been reported in the literature, always in patients who underwent pelvic radiation for gynecological cancers. 11 Histologically, angiosarcoma is composed of irregular anastomosing vascular channels and exhibits an invasive growth pattern, with frequent mitotic figures, cellular pleomorphism, and areas of necrosis. Masson's tumor, instead, presents a single layer of endothelial cells without nuclear anaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective series, however, report low rates of isolated regional nodal failure (RNF), suggesting that perhaps routine RNI may not be necessary (6)(7)(8)(9). Moreover, RNI is not without potential complications, including radiation pneumonitis (10), arm lymphedema (11), long-term cardiotoxicity (12), brachial plexopathy (13), and secondary cancers (14,15). Therefore the risk of RNI should be weighed against an individual's predicted risk of RNF based on available clinical, pathologic, and molecular factors.…”
Section: Introductionmentioning
confidence: 97%
“…However, a recent retrospective study of Finnish cancer patients showed different results (Virtanen et al 2007). Surveying more than 300,000 cancer patient records accrued over a 50-year period, Virtanen et al (2007) failed to identify a statistically significant association of AS with prior radiation treatment.…”
Section: Iatrogenic Asmentioning
confidence: 99%
“…Surveying more than 300,000 cancer patient records accrued over a 50-year period, Virtanen et al (2007) failed to identify a statistically significant association of AS with prior radiation treatment. These results agree with an earlier Swedish study of 122,991 women with breast cancer that showed no statistically significant correlation between radiation therapy and angiosarcoma, although they did observe a correlation with lymphedema (Karlsson et al 1998).…”
Section: Iatrogenic Asmentioning
confidence: 99%